2020
DOI: 10.1002/stc.2519
|View full text |Cite
|
Sign up to set email alerts
|

Seismic response prediction method for building structures using convolutional neural network

Abstract: Summary In this study, a method of predicting the seismic responses of building structures based on a convolutional neural network (CNN) is proposed. In the method, the time histories of acceleration responses previously measured in a building during earthquakes are used in the CNN input layer, with the corresponding time histories of the displacement responses being used in the CNN output layer. The correlations between the features automatically extracted from the acceleration responses by the convolution an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…Therefore, in the fitness evaluation of one individual in the solution group within one generation, that is, the CNN training, the training was set to stop early. In the author's previous studies [13], [14], it was confirmed that in the case of a CNN for prediction using measured structural responses, as in this study, training proceeds with a sharp decrease in the loss function value in the early stages of the training process. Therefore, based on the premature convergence characteristics of the CNN for the structural response estimation, this research method allowed the CNN training of one individual in the solution group to stop in its early stages, which can reduce the huge computational costs that can be incurred in the GA optimization process that operates multiple solutions.…”
Section: B Multi-objective Optimizationsupporting
confidence: 84%
See 3 more Smart Citations
“…Therefore, in the fitness evaluation of one individual in the solution group within one generation, that is, the CNN training, the training was set to stop early. In the author's previous studies [13], [14], it was confirmed that in the case of a CNN for prediction using measured structural responses, as in this study, training proceeds with a sharp decrease in the loss function value in the early stages of the training process. Therefore, based on the premature convergence characteristics of the CNN for the structural response estimation, this research method allowed the CNN training of one individual in the solution group to stop in its early stages, which can reduce the huge computational costs that can be incurred in the GA optimization process that operates multiple solutions.…”
Section: B Multi-objective Optimizationsupporting
confidence: 84%
“…Convolutional neural networks (CNN), which are deep learning algorithms, are actively being used in various research fields due to their excellent performance. For example, they have been used to build a structural response estimation model using measured structural responses in advance, and predict the structural responses when sensing is impossible or when data loss occurs [13], [14]. CNN was also used to predict the lateral displacement of a structure, which indicates the seismic performance of the structure, by identifying the relationship between the displacement and the acceleration structural response, which CNN can measure relatively easily [13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, some researchers combined other responses data (e.g., displacement or strain) with acceleration responses to evaluate the structures [ 26 , 27 , 28 , 29 ]. Moreover, Oh et al [ 30 ] used a convolutional neural network to predict the time histories of relative displacements from the recorded absolute accelerations, but relative error of the maxima (up to 16%) in the numerical simulation was unsatisfactory. Sun et al [ 31 ] used kernel-based machine-learning methods to estimate the seismic response demands, such as peak inter-story drift.…”
Section: Introductionmentioning
confidence: 99%